Pengaruh Inflasi, Pertumbuhan Ekonomi, Upah Minimum, dan Penyerapan Tenaga Kerja Terhadap Pengangguran Terbuka Di Provinsi Banten Tahun 2000-2020 - Fandi Chandra Irawan (Jurnal Ilmu Ekonomi, 2022)
This study aims to analyze employment conditions and how inflation affects economic growth, minimum wages and employment in Banten Province. The object of this research is focused on Banten Province with data published by BPS Banten province. The data collection method used is a study of documentation derived from the publications of the Central Statistics Agency. The data analysis method used is quantitative analysis in the form of time series multiple linear regression analysis based on classical assumption testing. The results of this study indicate that there is a positive and significant influence on inflation, economic growth, minimum wages and employment on unemployment in Banten Province. The results of further research show that inflation, economic growth, minimum wages on unemployment in Banten Province simultaneously or together. The suggestion of this research is to encourage local governments to increase the capacity of human resources that can increase productivity, economic growth, employment and pay attention to unemployment in Banten Province. So as to reduce the number of unemployed in Banten Province